Acute urinary retention in a young man secondary to colonic irrigation: a case report - LYNCH, THOMAS HUGH; RAHEEM, OMER (BioMed Central, 2009)
Introduction Autonomic innervation of the bladder is complex and regulated by a hierarchy of mechanisms of the central nervous system. Any dysfunction in these regulatory mechanisms can lead to acute urinary retention. Case presentation A 36-year-old Caucasian man presented with acute urinary retention following extensive bowel irrigation. His urinary bladder was decompressed and his normal voiding mechanism was restored thereafter. Conclusion We postulate that prolonged anorectal and sigmoid dilatation can stimulate the recto-vesicourethral reflex and lead to acute urinary retention via autonomic dysfunction.
PUBLISHED
Keywords: Surgery